Analisis Kinerja Guru Dalam Lesson Study Dan Self-Learning Siswa Pada Mata Pelajaran Dasar-Dasar Teknik Otomotif Di SMK Negeri I Palangka Raya - Debora Debora; Supriyadi Supriyadi; Ahmad Eko Suryanto; Ratna Pancawati; Vontas Alfenny Nahan; Harie Satiyadi Jaya; Erfandi Reinaldo; Ferdi Aridinata (Jurnal Ilmiah Kanderang Tingang, 2023)
This research aims to analyse teachers' performance in Lesson Study implementation and its impact on students' self-learning in Basic Automotive Engineering subject at SMK Negeri 1 Palangkla Raya. Lesson Study is a method of developing teacher professionalism that focuses on planning, observing, and reflecting on learning, while students' self-learning to learn independently. The research was conducted using qualitative methods and data were obtained through classroom observations, interviews with teachers, and questionnaires to students. The results showed that the teacher's performance in implementing lesson planning, the use of teaching materials and the effectiveness of learning is very good, only in technical skills and the application of learning strategies that are still lacking and need to be improved. Meanwhile, students' self-learning tends to be low which is inversely proportional to teachers' self-learning which tends to be high.